The morphology-controlled deposition of ZnO nanocrystalline. (January 2019) - Zhou, D; Wang, L N; Liu, J T; Yu, Y; Luan, Z Q; Gao, Z H; Jin, G Y; Chen, Y T; Huang, W Z
Abstract: The ZnO nanocrystalline was deposited on quartz substrate by a CVD method. Our investigation proves that the morphology-controlled deposition of nanocrystalline can be realized by adjusting the substrate temperature. The nanocrystalline consisted of nanorods, nanobulks and nanowires. It turns out that higher temperatures are more favorable for the foration of nanorods and nanowires, while lower ones promote the formation of nanobulks. The SEM and XRD methods were used to characterize the microstructural properties of the sample. The produced nanorods were about 6.25-28.25μm in length with great uniformity. An intense 002 peak was observed, which indicated that nanorods had a strongly pronounced hexagonal wurtzite structure, while the lattice parameter was very close to its theoretical value.